IDENTIFICATION OF POSSIBLE MOLECULAR TARGETS OF POTENTIAL ANTI-PARKINSON DRUGS BY PREDICTING THEIR BINDING AFFINITIES USING MOLECULAR DOCKING TECHNIQUE - Dorice, Maguemga Homsi Chanceline; Khurana, Navneet; Sharma, Neha; Khatik, Gopal L (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Mechanistic study of newly reported anti-Parkinson agents by molecular docking to predict possible target. Methods: Structures of newer drugs known anti-Parkinson agents were drawn using ChemBioDraw 2D software. Thereafter, they were converted to 3D structures using ChemBioDraw 3D software in which they were subjected to energy minimization using the MM2 method and then saved as PDB extension files, which can be accessed using the AutoDock Vina (ADT) interface. ADT 1.5.6 software version was used for molecular docking study. Results: Various molecular targets were selected (D2/D3, D2, A2A, and MAO-B) and studied for Pardoprunox, Istradefylline, Rasagiline, and Bromocriptine. Pardoprunox, Istradefylline, and Bromocriptine had more affinity with their corresponding receptor with −6.9, −8.5, and −9.4 kcal/mol binding affinity, respectively, except Rasagiline, who has less affinity with its corresponding receptor (−6.4kcal/mol) and shown better affinity with 3pbl receptor (−6.7 kcal/mol). Conclusion: Pardoprunox, Istradefylline, and Bromocriptine were found to act on D2/D3 (3pbl), A2A (3pwh), and D2 (4yyw), respectively, whereas Rasagiline found to be act on D2/D3 (3pbl) receptor. The results help in prediction of mechanism and interaction to various Parkinson's disease targets.